2022
DOI: 10.1111/jre.12977
|View full text |Cite
|
Sign up to set email alerts
|

Periodontitis is associated with higher subclinical atherosclerosis in patients with systemic lupus erythematosus

Abstract: Aim: To determine periodontitis prevalence in patients with systemic lupus erythematosus (SLE) and to assess whether periodontitis in SLE patients is associated with a greater subclinical atherosclerosis. Methods: An observational case-control study was conducted in SLE (cases) and patients without any rheumatic diseases (controls), matched for sex. Sociodemographic and cardiometabolic variables were gathered, and SLE activity was assessed through several indexes. Periodontal examination registered probing poc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…For the latter, some studies have shown the association of high concentrations of the odontopathogenic Porphyromonas gingivalis ( Pg ) and the commensal and periodontal pathogen Fusobacterium nucleatum ( Fn ) and periodontitis with clinical and experimental atherosclerosis [ 15 ]. Interestingly, greater subclinical carotid atherosclerosis has been reported to be associated with periodontitis in patients with systemic lupus erythematosus [ 16 ]. Moreover, periodontitis was found to be a significant risk factor for peripheral and carotid ASCVD in meta-analyses including large populations [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the latter, some studies have shown the association of high concentrations of the odontopathogenic Porphyromonas gingivalis ( Pg ) and the commensal and periodontal pathogen Fusobacterium nucleatum ( Fn ) and periodontitis with clinical and experimental atherosclerosis [ 15 ]. Interestingly, greater subclinical carotid atherosclerosis has been reported to be associated with periodontitis in patients with systemic lupus erythematosus [ 16 ]. Moreover, periodontitis was found to be a significant risk factor for peripheral and carotid ASCVD in meta-analyses including large populations [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%